Pengaruh Substitusi Tepung Ubi Jalar Kuning Dan Kedelai Pada Kue Putu Ayu - By Khoir, Sampurna Kabir; Susanti, Ambar; Chusnah, Miftachul (Exact Papers in Compilation (EPiC), 2022)
The need for wheat flour in Indonesia is increasing along with the increasing types of processed flour. The purpose of this study was to determine the appropriate concentration of yellow sweet potato and soybean flour in order to obtain the putu ayu cake with good and favorable properties. This study used a one-factor Completely Randomized Design (CRD) with a comparison of the concentrations of wheat flour, yellow sweet potato, and soybean which consisted of four treatments, namely K (100%: 0%: 0%), L (50%: 40%: 10%), M (50%:45%:5%), and N (50%:35%:15%). Each treatment has a total flour weight of 250 grams. Data collection used a 15 panelist questionnaire method with 3 replications for each sample. Furthermore, scoring and analysis using ANOVA with further test BNT level 5%. The results showed that putu ayu cake in treatment M had a rather attractive color, delicious aroma, soft texture, and a slightly sweet savory taste, compared to treatment L which had a rather attractive color, delicious aroma, soft texture, and slightly sweet taste. The color N treatment is rather attractive, the aroma is rather pleasant, the texture is slightly rough, and the taste is slightly savory - slightly sweet. The best and preferred substitution of yellow sweet potato flour and soybean flour is treatment concentration M (45%:5%).